Zoning-Based System of New Students Admission Policy - Rahmawati Rasinan; Sugiarto Sugiarto; Matin Matin (STAI Hubbulwathan Duri, 2021)
The zoning system in accepting new students is the government's effort to build quality, fair and equitable education. The purpose of the study was to obtain in-depth information about the implementation of the zoning system in the acceptance of new students in Jakarta. This study used a descriptive qualitative tentative approach. Data were collected through interviews, observation and documentation. Data analysis techniques consist of data reduction, data presentation, and conclusion drawing/verification. The study results concluded that the implementation of the zoning system in the acceptance of new students was quite good and provided equal opportunities for all prospective students according to the right selection path. While the problems complained about are related to the internet network and also fraud committed by some people. However, the results of this study have an impact on improving the more equitable zoning system.